Pacific Agriculture and Forestry Policy Network (PAFPNet) Strategic Plan 2010–2012 - Secretariat of the Pacific Community (SPC, 2010)
To support the network in future, and to ensure PAFPNet is focused on issues of strategic importance to its members, this Strategic Plan was developed at its second stakeholder meeting in December 2009. Members of the network present re-examined the network’s original goals and objectives to ensure they remained valid, and identified key objectives and outputs for the network over the next three years (2010 to 2012).